Prediction of shear capacity of UHPC – concrete composite structural members based on existing codes - Yin, Hor; Shirai, Kazutaka; Teo, Wee (Journal of Civil Engineering and Management, 2018)
Reinforced concrete (RC) structural members strengthened with ultrahigh-performance concrete (UHPC) have shown excellent performance in past experimental investigations. However, methods of predicting their capacity are currently very limited. This paper presents six independent methods of predicting the shear capacity of UHPC–concrete composite members based on the application of existing design codes. Three of these methods are based on the conversion of the volume fraction of steel fibres in the UHPC in an equivalent longitudinal steel ratio. The other three methods involve the computation of the shear strength as a sum of the contributions to the shear strength by the RC member and the UHPC layer, each of which is independently calculated. It was demonstrated that the proposed methods based on existing design codes are able to predict the strength of UHPC–concrete composite members with reasonable accuracy.